Employability of Persons With Mental Disability: Understanding Lived Experiences in Kenya - Ebuenyi, Ikenna D.; Guxens, Mònica; Ombati, Elizabeth; Bunders-Aelen, Joske F. G.; Regeer, Barbara J. (Frontiers in Psychiatry, 2019)
Introduction: Globally, mental illness affects social and occupational functioning. We aimed to highlight the barriers to employment experienced by persons with mental disabilities in Kenya and how they manage to find work against all the odds. Materials and Methods: Using a mixed-method study design, we purposely sampled persons with mental illness through networks of persons with psychosocial disabilities (Users and Survivors of Psychiatry and African Mental Health Foundation, Kenya). Qualitative data was obtained through in-depth interviews (n=14) and four focus group discussions (n=30) while a researcher-designed questionnaire was used to obtain quantitative data (n=72). Results: We identified five major clusters of barriers to employment: mental illness factors, social exclusion and stigma, work identity crisis, non-accommodative environment and socioeconomic status. Factors that facilitated employment include self-awareness and acceptance, self-employment, provision of reasonable accommodation, improved health services, addressing discriminatory laws and practices and social development programmes and support. Participants considered psychiatric illness the highest barrier to employment (63.2%), while a supportive family/friends was considered the highest facilitator of employment (54.5%). Conclusion: The employment experiences of persons with mental disabilities are influenced by various interrelated factors in their social environment. Proactive social support and affirmative action by government may improve their employment opportunities and quality of life.